2004
DOI: 10.1074/jbc.m311886200
|View full text |Cite
|
Sign up to set email alerts
|

An Oriented Peptide Array Library (OPAL) Strategy to Study Protein-Protein Interactions

Abstract: One of the major questions in signal transduction is how the specificities of protein-protein interactions determine the assembly of distinct signaling complexes in response to stimuli. Several peptide library methods have been developed and widely used to study proteinprotein interactions. These approaches primarily rely on peptide or DNA sequencing to identify the peptide or consensus motif for binding and may prove too costly or difficult to accommodate high throughput applications. We report here an orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 34 publications
1
89
0
1
Order By: Relevance
“…Second, the template used for positional scanning is an oriented peptide library (OPL, alternatively referred to as an oriented degenerate peptide) (12,20,25), consisting of two anchor residues and many degenerate residues. The two anchor residues (typically R at PϪ3 and F at Pϩ1) provide sufficient favorable interaction of the investigated kinases to all peptide substrates to permit measurable phosphorylation of each peptide pool; the remaining degenerate positions provide diversity, which ensures that the residue preference measured pertains to diverse sequences (rather than to a single peptide, as is the case for most positional scanning studies of peptide specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the template used for positional scanning is an oriented peptide library (OPL, alternatively referred to as an oriented degenerate peptide) (12,20,25), consisting of two anchor residues and many degenerate residues. The two anchor residues (typically R at PϪ3 and F at Pϩ1) provide sufficient favorable interaction of the investigated kinases to all peptide substrates to permit measurable phosphorylation of each peptide pool; the remaining degenerate positions provide diversity, which ensures that the residue preference measured pertains to diverse sequences (rather than to a single peptide, as is the case for most positional scanning studies of peptide specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies examining SH2 domain specificity have generally identified only a small number of critical residues that are required for the interaction between a given SH2 domain and its cognate phosphopeptide ligands (11,12). Although peptide library-based studies reveal limited specificity (10,14,15), anecdotal evidence from physiological interactions suggests that specificity is more complex. Despite these intense studies, the true selectivity of SH2 domains for physiological peptide ligands may not yet be fully appreciated.…”
Section: The Src Homology 2 (Sh2)mentioning
confidence: 99%
“…Pioneering studies by Songyang and co-workers (10,14,15,20) and others (19,21) using degenerate peptide libraries and related techniques established broad specificity profiles for a wide range of SH2 domains. These approaches capture general binding motifs through paneling individual positions (for example at ϩ1 or ϩ2 residues C-terminal from the phosphotyrosine) independently of neighboring positions.…”
mentioning
confidence: 99%
“…OPAL and Permutation Array-The OPAL was described by Rodriguez et al (22). The peptide arrays were generated on cellulose membranes using an Intavis Multipep instrument (Intavis, Germany) and Fmoc (N-(9-fluorenyl)methoxycarbonyl)-based chemistry according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…There are three potential O-glycosylation regions (25). Two of them ( 19 SSPS 22 and 75 TTTRNTVCQCEEGT 88 ) are in the common ECD sequence of mature human DR5 splice variants, and the third is located within the alternatively spliced DR5 region. However, the effect of O-glycosylation modification on the DR5-AD5-10 complex can be ignored in our study because AD5-10 was generated by immunizing mice with recombinant DR5a expressed in Escherichia coli.…”
Section: Novel Death-inducing Region Is Located Within the Dr5 N-termmentioning
confidence: 99%